Aide internationale et grands projets urbains en Afrique sub-saharienne. Le cas de la Ville du rail à Nairobi - Bérénice Bon (Cybergeo, 2020)
Sub-Saharan African cities are characterized by a diversification of international urban cooperation with the intervention of multiple foreign donors, and a significant increase of the markets for urban expertise. Between 2018 and 2019, $148 million was invested in the capital city of Kenya, Nairobi. Through the case study of the Railway City in Nairobi, this article questions the negotiation and decision-making processes of megaprojects in sub-Saharan African cities, in the context of a high dependency on external funding. We take a dive into the institutional mechanisms, discursive registers, and avoidance plays through which national and international actors legitimize their actions in the instruction phase of a megaproject. This paper shows that these international cooperations represent resources for local action, but also stir up competition and can have disruptive effects for urban governance.